An integrated multiscale air quality modelling framework for industrial park pollution: Linking local emissions to regional transport - Tao Wang; Jie Li; Joshua S. Fu; Wei Wang; Bing Liu; Bin Zhao; Yibo Zhang; Jinxiu Pan; Feng Sun; Xiu’e Shen; Zhe Wang; Xiao Tang; et al. (Journal of Environmental Sciences, 2026)

Efficacy and safety of natural killer cell therapy for the treatment of advanced non-small cell lung cancer: A meta-analysis and systematic review - Zhengnan Li; Xiu’e Wang; Shaoqing Chen; Ping Zhang; Xiujuan Wang; Xinye Ni; Chunlin Mou (Immunologic Research, 2025)
To evaluate the efficacy and safety of natural killer (NK) cell therapy for the treatment of advanced non-small cell lung cancer (NSCLC). Relevant studies on NK cell therapy for advanced NSCLC were collected from PubMed, Scopus, Embase and the Cochrane Library up to August, 2024. Two reviewers independently screened the articles and retrieved the data using the Cochrane risk assessment tool. Meta-analysis was conducted with R (version 4.3.1). A total of nine trials were analyzed, including five phase 2 randomized controlled and four phase 1 studies. All were medium to high quality but exhibited high performance and attrition biases. NK cell treatment doses ranged from 1×10 9 to 4×10 9 cells for 2 or 3 cycles. In total, 324 patients with advanced NSCLC were included, comprising 199 who received NK cell therapy and 125 controls, all previously treated with platinum-based regimens. Meta-analysis demonstrated comparable disease control (OR = 2.68; 95% CI: 1.53–4.71) and 1-year survival (OR = 2.54; 95% CI: 1.28–5.02) between groups, with similar adverse events rates (OR = 1.37; 95% CI: 0.35–5.26). Subgroup analyses revealed no significant differences in efficacy. There was considerable heterogeneity among studies ( I ² = 0%–92.5%). Over 39 trials were registered, with only 12 marked as completed and none of the others released the outcome data. Current evidence suggests that NK cell therapy, either alone or in combination, may achieve disease control, survival outcomes and safety profiles that were comparable to existing treatments for advanced NSCLC. These findings remain exploratory and should be confirmed in larger, well-designed trials.

Construction of a thermosensitive gel based on hydroxypropyl-β-cyclodextrin/meloxicam inclusion complexes for improving meloxicam solubility and prolonging drug retention time in the cornea - Lvyao Yang; Xiu’e Li; Yuanke Zhang; Jingjing Tian; Guixia Ling; Peng Zhang (Drug Delivery and Translational Research, 2025)

The effect of heatwave and cold spell on cardiovascular disease mortality in central China, 2018–2022 - Ling-Shuang Lv; Li Yin; Yuan Liu; Chun-Liang Zhou; Ji Hu; Ning An; Xian Xie; Xing-E Zhang; Min Zhang; Xiu-Ying Liu (International Journal of Biometeorology, 2025)

Genome-wide identification of the sugar beet (Beta vulgaris L.) DMP gene family and its potential role in abiotic stress - Pingan Han; Yue Chang; Kuangang Tang; Liang Wang; Zhijun Xiu; Jing Yang; Haibo Shi; Yahui Liang; Ruifen Sun; Shaofeng Su; Ziqiang Zhang; Zengjuan Fu; et al. (Genetic Resources and Crop Evolution, 2025)

Tyrobp deficiency blocks NLRP3-mediated inflammation and pyroptosis to alleviate myocardial ischemia-reperfusion injury through regulating Syk - Jie Yu; Xiu’e Mu; Chang Guan; Yaqin Wang; Hongying Li (Tissue and Cell, 2024)

Biological characteristics of Cordyceps militaris single mating-type strains - Xiu’E Li; Xin Wang; Fengji Liang; Zhaoxin Wang; Wenshuo Liu; Yupeng Ge; Shude Yang; Yu Liu; Yin Li; Xianhao Cheng; Weihuan Li (Archives of Microbiology, 2024)

Peacock flaunting tail inspired-multiple interactions between black phosphorene and glass powder with safety shield fire of epoxy resin - Kunxin Wang; Guoming Yuan; Zhijun Liu; Hui Yang; Yang Li; Xiu-e Li; Kun Wu; Jun Shi (Chemical Engineering Journal, 2024)

Triphenylpyrazoline ketone chlorophenols as potential candidate compounds against Parkinson’s disease: design, synthesis, and biological evaluation - Ning Ning Cheng; Le Hua Zhang; Rui Ge; Xiu E. Feng; Qing Shan Li (Medicinal Chemistry Research, 2022)

PSD-93 Interacts with SynGAP and Promotes SynGAP Ubiquitination and Ischemic Brain Injury in Mice - Qingxiu Zhang; Hui Yang; Hong Gao; Xiaomei Liu; Qingjie Li; Rong Rong; Zhenqian Liu; Xiu-e Wei; Liping Kong; Yun Xu; Liangqun Rong (Translational Stroke Research, 2020)

Fluorophenols bearing nitrogenated heterocycle moieties, a class of novel Keap1-Nrf2 protein-protein interaction inhibitors: synthesis, antioxidant stress screening and molecular docking - Xiu E Feng; De Peng Kong; Shu Rong Ban; Rui Ge; Qing Shan Li (Medicinal Chemistry Research, 2019)

Anxiolytic potency of iridoid fraction extracted from Valeriana jatamansi Jones and its mechanism: a preliminary study - Xue-Mei Zhang; Jia-Li Zhu; Yong Sun; Yao-Lan Dai; Xiu Chen; Jia-Hong Cao; Ruo-Cong Yang; Chang Chen; Chao-Ying Ma; Tian-E Zhang; Yun-Hui Chen; Zhi-Yong Yan (Natural Product Research, 2018)

An UDP-Glucosyltransferase Gene from Barley Confers Disease Resistance to Fusarium Head Blight - Li-Ping Xing; Li-Qiang He; Jin Xiao; Qi-Guang Chen; Ming-Hao Li; Yi Shang; Yan-Fei Zhu; Pei-Du Chen; Ai-Zhong Cao; Xiu-E Wang (Plant Molecular Biology Reporter, 2017)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

Organic carbon mineralization responses to temperature increases in subtropical paddy soils - Ping Zhou; Yong Li; Xiu’e Ren; He’ai Xiao; Chengli Tong; Tida Ge; Philip C. Brookes; Jianlin Shen; Jinshui Wu (Journal of Soils and Sediments, 2014)

Immunohistochemical characterisation of differentiated CAD cells: expression of peptides and chromogranins - Yongling Li; Linda Xiu-E Hou; Annika Aktiv; Annica Dahlström (Histochemistry and Cell Biology, 2005)

High-efficiency regnerationin vitro from potato petioles with intact leaflets - Shirley Yee; Birt Stevens; Shirlyn Coleman; Jane E. A. Seabrook; Xiu-Qing Li (American Journal of Potato Research, 2001)